Seismic responses of isolated bridges subjected to near-fault ground motions: simple pulses vs. whole records - Hui, Ying-Xin; Wang, Jie; Lv, Jia-Le; Xu, Ting-Ting (Frontiers in Built Environment, 2024)
Velocity pulse with strong energy input is the significant feature of near-fault ground motions. Bridges close to or passing across seismic faults may suffer from higher failure risk, which is inseparable from the influence of velocity pulse. This study aims to evaluate the nonlinear response characteristics of bridge structures under various near-fault ground motion conditions. A typical isolated continuous girder bridge is adopted, and two corresponding finite element models, i.e., considering and ignoring the heating effect of lead core bearings (LRBs), are established based on the OpenSees platform. Then, a total of 40 near-fault ground motion records are selected, and the pulses are extracted. Both the energy-based and deformation-based seismic responses are captured and compared to reveal the differences for the isolated bridge subjected to the original waves and the extracted pulses. The results highlight that the accuracy of the seismic evaluation based on the extracted pulses strongly depends on the precondition that the pulse period is close to the fundamental period of the isolated bridge. Hence, inputting the extracted pulses for predicting the in-elastic seismic response of isolated bridges locating at near-fault region is not an adequate replacement for those original waves of near-fault ground motions. In addition, the heating effect of LRBs will be magnified for the seismic response of isolated bridges subjected to the extracted pulses, and it will mainly affect the seismic responses of bearings and piers, i.e., the former increases and the latter decreases.